Pengaruh Motivasi, Kepemimpinan, Kompetensi Terhadap Produktivitas Kerja Pegawai PT. PLN (Persero) Area Tanjungpinang - Tiurma Arta Uli; Winata Wira; Dodi Dermawan (Bahtera Inovasi, 2018)
This study aims to determine whether motivation, leadership and competence affect the work productivity of employees of PT. PLN (Persero) Tanjung Pinang Area. The type of data used is primary data and secondary data obtained through interviews, questionnaires and literature studies whose measurements use a Likert scale and processed with the SPSS22 program. The sample technique used purposive sampling amounting to 74 respondents distributed to all permanent employees of PT PLN (Persero) Tanjungpinang Area. The data analysis method used is quantitative analysis using data quality test, classic test and multiple linear regression analysis. The results of this study indicate that simultaneously motivation, leadership and competence have a significant effect on the work productivity of employees of PT PLN (Persero) Tanjungpinang Area. In partial testing (t test) motivation does not have a significant effect on the productivity of employees of PT PLN (Persero) Tanjungpinang Area. Partial leadership has a significant effect on the productivity of employees of PT PLN (Persero) Tanjungpinang Area. Partial competence does not have a significant effect on work productivity of PT. PLN (Persero) Tanjungpinang Area employees